Study on the flexural behavior of poplar beams externally strengthened by BFRP strips - Qing Liu; Shengqiang Ma; Xia Han (Journal of Wood Science, 2020)
Abstract Poplar plants with peculiar characteristics grow extensively and naturally in the Northern Hemisphere, and such poplar is the main timber material in Xinjiang, China. However, poplar has defects that affect its ultimate bearing capacity. This study investigates the flexural behavior of the timber members from poplar. Three lengths of basalt fiber-reinforced polymer (BFRP) strips were used to strengthen timber beams from poplar with rectangular cross-sections. From the experimental data, the timber beams strengthened by 1900-mm-long and 50-mm-wide BFRP strips showed the best ultimate bearing capacity and maximum deflection of mid-span compared with the other two strengthened beams. The increments were 77.8% and 110.1% compared with the control beam. The assumption “plane section remains plane” remains practicable in the poplar beams bonded by BFRP strips, and the neutral axis of the strengthened beams had a tendency to move toward the tensile zone. Furthermore, the processes of the flexural behavior of the specimens were simulated by finite element analysis modeling, but all the analyzed values of ultimate bearing capacity and deflection of the beams are higher than those of the experiment. These values can roughly be used as reference for experimental results. However, accurate modeling should be developed and modified in subsequent research on timber beams from Xinjiang poplar.